Suatu Analisis Pengaruh Pemasaran Digital dan Variasi Produk Terhadap Perkembangan UMKM di Masa Pandemi COVID-19 (Survey Terhadap Pelaku UMKM di Provinsi Banten): The Influence of Digital Marketing and Product Variations on the Development of MSMEs during the COVID-19 Pandemic (Survey of MSME Actors in Banten Province) - Baghas Budi Wicaksono (Sains Manajemen: Jurnal Manajemen Unsera, 2022)
This study aims to determine the effect of product variations in the MSME sector and digital marketing on the development of the MSME sector in Banten Province. The data in this study were obtained primarily through questionnaires given to more than 50 respondents spread across the Regency/City of Banten Province. This study uses a quantitative approach through the Ordinary Least Square analysis method with the classical assumption test. The study results indicate a positive and significant influence between product variations and digital marketing on the development of the MSME sector. This is indicated by the t-statistic value which has a p-value <0.05. The research model is also free from classical assumption problems (homoscedasticity, normal distribution, non-multicollinearity, and non-autocorrelation). The R-Squared value of 0.97 indicates that variations in the development of the MSME sector in Banten Province can be explained by variations in products and digital marketing of 97%. That is, there is a 3% variation in the development of the MSME sector which is explained by variables other than those studied in this research model.